Authentic Leadership: Strategy of the Implementation of Madrasah Management of Change - Komariah, Aan; Kurniady, Dedy Achmad (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
Implementing the management of madrasah change starts from an authentic leadership. Authentic leadership is the identity of ahead of madrasah in developing a value-based educational system. His identity is seen from his sincerity in working, his kindness in treating people, and the sharpness of his mind in determining the future of the organization. The authentic leadership of madrasah should represent the identity of Muslim morality with work orientation on the sincerity of being a STAF+B (Siddiq, Tablig, Amanah, Fathonah + Brave) leader. Leading the madrasah in the context of implementing management of change is not enough to be pious but it requires courage to take strategic and innovative decisions in realizing a qualified madrasah. This research aims to find an authentic leadership strategy model for the management of change by the head of the madrasah. The research was conducted on the head of the madrasah in Pangandaran Regency. The results show that the application of authentic leadership can build madrasah changes by empowering the Professional Learning Community (PLC) in which 4CS strategy is implemented in a reciprocal (cumsuis-Casing, Communicating, Competencies, Contribution, Sample). The followers can identify who the authentic leader is by finding the integrity of identity that represents in: his mind is vision; his heart is good and his legs work hard.